2013
DOI: 10.1007/s12687-013-0154-0
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to participate in genomics research and desire for personal results among underrepresented minority patients: a structured interview study

Abstract: Patients from traditionally underrepresented communities need to be involved in discussions around genomics research including attitudes towards participation and receiving personal results. Structured interviews, including openended and closed-ended questions, were conducted with 205 patients in an inner-city hospital outpatient clinic: 48 % of participants self-identified as Black or African American, 29 % Hispanic, 10 % White; 49 % had an annual household income of <$20,000. When the potential for personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 56 publications
6
69
1
Order By: Relevance
“…Finally, our finding that two thirds of these overweight individuals were interested in receiving personalized genetic information about their own and their children's obesity risk adds to the few previous studies that have found high levels of interest in genetic testing for obesity among clinical populations [63,64] , albeit at lower levels than for other diseases such as heart disease, type 2 diabetes, and cancer [65] . We speculate that perhaps the high level of interest in genetic testing for obesity risk observed in the present study is due to overweight people believing that if they obtain a 'high-risk' result from genetic testing for obesity risk, this could explain their struggles with weight.…”
Section: Discussionsupporting
confidence: 55%
“…Finally, our finding that two thirds of these overweight individuals were interested in receiving personalized genetic information about their own and their children's obesity risk adds to the few previous studies that have found high levels of interest in genetic testing for obesity among clinical populations [63,64] , albeit at lower levels than for other diseases such as heart disease, type 2 diabetes, and cancer [65] . We speculate that perhaps the high level of interest in genetic testing for obesity risk observed in the present study is due to overweight people believing that if they obtain a 'high-risk' result from genetic testing for obesity risk, this could explain their struggles with weight.…”
Section: Discussionsupporting
confidence: 55%
“…However, providing an incentive decreased the odds of consenting to allow sharing with other NIH investigators, even when other factors associated with sharing were held constant. Perhaps, people willing to donate a sample without any kind of incentive are more altruistic and already open to granting permission to share (Sanderson et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, research experience has found incongruence between the stated willingness to donate a biological sample and the actual participation rates in genetic research (Johnsson et al 2010). Studies around the world often find at least 80 % of people state that they are willing to donate biological material for research purposes (Wendler 2006;Sanderson et al 2013); however, the actual participation rates for genetic and biobank research can be closer to half of the rate of reported willingness (Johnsson et al 2010), although some efforts have had high actual participation (McQuillan et al 2003). In studies recruiting from general population or community samples, participation rates are lower when a consent form mentions the study of genes and DNA (Matsui et al 2005;McQuillan et al 2006;Melas et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paucity of minority representation in biomedical research has fostered global, national, and local collaborations to identify major contributions and best practices to address this systemic problem [18]. Some of the salient reasons minority populations remain underrepresented in biomedical research include the following: the mistrust of the medical community [9, 10], misperceptions of biomedical research [11], employment of unsuccessful and inconsistent recruitment strategies [10], lack of awareness of studies for which minorities are eligible [12], and lack of research studies that incorporate non-invasive methods preferred by minority populations [6, 13]. As we learn more about the direct impact of biological and genetic contributions to health outcomes, it will be equally as important to focus on issues that inadvertently exacerbate disparities such as the underrepresentation of minorities in biomedical research.…”
Section: Introductionmentioning
confidence: 99%